Self concept, self control, labelling and preceptions of delinquent behaviours : a case study on residents of Rumah Victory in Kuala Lumpur and Monfort Boys Town in Shah Alam, Selangor Darul Ehsan - Tan, Hui Theng (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
This is a qualitative study on the perceptions of respondents from the Youth Life Renewal Centre of Rumah Victory, Kuala Lumpur and the Montfort Boys Town, Shah Alam on juvenile delinquency. The objectives of the study are to find out perceptions of the respondents on delinquency before and after their participation in the rehabilitation programme at Rumah Victory and the character building programme at Montfort Boys Town by focusing on the influence of self concept, self control and labelling on perceptions of the respondents and their behaviours, as well as to find out the meaning or definition of delinquent behaviours from the respondents. The study was carried out from July 2006 to November 2007. The sample of this study consists of eleven residents from Rumah Victory and ten residents from the Montfort Boys Town. In-depth interview, non-participatory observation and comparative study were the methods used in the process of collecting and analysing data. The topics discussed were related to the meaning or definition of delinquent behaviours based on the perceptions of the respondents as well as their perceptions on self concept, self control, labelling and delinquent behaviours before and after their admission to the two institutions. The respondents define delinquency as a source of excitement and fun, means to get money, a source of help and protection, a way to solve problem, means to get attention from parents, teachers and others, a form of escape from boredom, dysfunctional family and challenging undertaking like schooling, and a source of power. The findings indicate that delinquency is influenced by self concept, self control and labelling. The findings also show that there is a connection between self concept, self control and labelling that influences perceptions of the respondents. Such perceptions also affect their behaviours and behavioural change.